Compact Low-Loss Optical 72 $^{° }$ Hybrid Based on Nonoverlapping-Image Multimode Interference Coupler in Silicon-on-Insulator - Zezheng Li; Yingxin Kuang; Huan Guan; Yang Liu; Xinqun Zhang; Weihua Han; Zhiyong Li (IEEE Photonics Journal)
A universal principle to achieve different optical hybrids is summarized based on general nonoverlapping-image MMI couplers. An optical 72 $^{° }$ hybrid is proposed and demonstrated which is achieved by a 2 × 5 multimode interference (MMI) coupler with length of 89.5 $μ$ m and width of 8.0 $μ$ m. The device is fabricated in silicon-on-insulator (SOI) with 220 nm thick top silicon layer and the buried oxide layer is 3 $μ$ m thick. The proposed device exhibits an extinction ratio larger than 20 dB from 1470.8 nm to 1581.2 nm. The excess loss of optical hybrid is about 1.4 dB and a phase deviation less than $± 6.0^{° }$ is obtained with the bandwidth of 51.5 nm.